Synthesis , Characterization and Biological activity of new derivatives of Chromen-2-one (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
We report the organic syntheses of new derivatives  from Chromen-2-one and their  antibacterial activity. Compounds  4-[Acetyl-(2-oxo-2H-chromen-4-yl)-amino]-benzenesulfonyl chloride 1a, 4-[Acetyl-(2-oxo-3-phenylsulfamoyl-2H-chromen-4-yl)-amino]-benzenesulfonyl chloride 2a , 2-{4-[Acetyl-(4-chlorosulfonyl-phenyl)-amino]-2-oxo-3-phenylsulfamoyl-2H-chromen-7-ylamino}-benzoic acid  3a. All Structures have been synthesized and characterized using melting points , IR spectra , 1H-NMR, 13C-NMR spectra , and elemental analyses  . The purified synthesized compounds (1a,2a,3a), at contcentrations 2,3,5 mg/ml was tested for their  antibacterial activity against three bacterial cultures ;Staphylococcus aureus, Escherchia coli and Bacillus cereus. The antibacterial activity of synthesized compounds are compared with antibacterial activity of standard antibiotics cephalexine and streptomycine.  The compounds (1a,2a,3a) shows  different bacteriostatic and bacteriocidal activity.